Between tradition and renovation: Ángel González and rhetoric rewriting - Leuci, Veronica (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The present article proposes to approach the poetic work of Ángel González by the rewriting of rhetorical tradition. Specifically, we choose two discursive types, égloga and soneto, in order to see how those classic genres of the Spanish poetry are recovered by the present writers. The rhetoric, then, is thought like an extremely fruitful access road that allows to release fraternities, continuities and renovations with forms, topics, previous aesthetics, within the framework of a poetry that does not reject but rebuilds by a novel way that rich legacy.